A new assay for measuring chromosome instability (CIN) and identification of drugs that elevate CIN in cancer cells - Lee, Hee-Sheung (BioMed Central, 2013)
BACKGROUND: Aneuploidy is a feature of most cancer cells that is often accompanied by an elevated rate of chromosome mis-segregation termed chromosome instability (CIN). While CIN can act as a driver of cancer genome evolution and tumor progression, recent findings point to the existence of a threshold level beyond which CIN becomes a barrier to tumor growth and therefore can be exploited therapeutically. Drugs known to increase CIN beyond the therapeutic threshold are currently few in number, and the clinical promise of targeting the CIN phenotype warrants new screening efforts. However, none of the existing methods, including the in vitro micronuclei (MNi) assay, developed to quantify CIN, is entirely satisfactory. METHODS: We have developed a new assay for measuring CIN. This quantitative assay for chromosome mis-segregation is based on the use of a non-essential human artificial chromosome (HAC) carrying a constitutively expressed EGFP transgene. Thus, cells that inherit the HAC display green fluorescence, while cells lacking the HAC do not. This allows the measurement of HAC loss rate by routine flow cytometry. RESULTS: Using the HAC-based chromosome loss assay, we have analyzed several well-known anti-mitotic, spindle-targeting compounds, all of which have been reported to induce micronuclei formation and chromosome loss. For each drug, the rate of HAC loss was accurately measured by flow cytometry as a proportion of non-fluorescent cells in the cell population which was verified by FISH analysis. Based on our estimates, despite their similar cytotoxicity, the analyzed drugs affect the rates of HAC mis-segregation during mitotic divisions differently. The highest rate of HAC mis-segregation was observed for the microtubule-stabilizing drugs, taxol and peloruside A. CONCLUSION: Thus, this new and simple assay allows for a quick and efficient screen of hundreds of drugs to identify those affecting chromosome mis-segregation. It also allows ranking of compounds with the same or similar mechanism of action based on their effect on the rate of chromosome loss. The identification of new compounds that increase chromosome mis-segregation rates should expedite the development of new therapeutic strategies to target the CIN phenotype in cancer cells.